A compact balun‐diplexer using interdigital line resonators. Issue 6 (8th December 2014) - Chen, Jian‐Zhong; Shen, Jie; Gao, Ni; Chen, Jia
ABSTRACT A novel compact balun‐diplexer applying new interdigital line resonators (ILRs) is presented in this article. It is found that the proposed ILR can not only reduce circuit size and but also realize high common mode rejection in differential mode operation frequency. By properly converting the symmetric four‐port balanced bandpass filter (BPF) to a three‐port device, a balun BPF with high selectivity and compact size are accomplished using ILRs. Then, the balun‐diplexer can be realized by combining two well‐designed balun filters with two 50 Ω transmission lines. The demonstrated balun‐diplexer with operation at 1.8 and 2.45 GHz have been designed, fabricated, and measured. Excellent performances have been observed. Specifically, 0.4 dB in‐band amplitude error, 1.8 in‐band phase error, more than 50 dB selectivity and 45 dB isolation are obtained. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:485–489, 2015.